Ground warming releases inorganic mercury and increases net methylmercury production in two boreal peatland types - Sun, Ting; Lindo, Zoë; Branfireun, Brian A. (Frontiers in Environmental Science, 2023)
Boreal peatlands are considered sinks for atmospheric mercury (Hg) and are important sources of methylmercury (MeHg) to downstream ecosystems. Climate change-driven increases in average annual temperature in coming decades will be amplified at higher latitudes and will modify many biogeochemical processes in high boreal and subarctic peatlands that are important landscape features in these regions. Changes in water quality are an important issue for northern ecosystems and fish consumers, and the directionality of changes in mercury levels due to climate warming presents considerable uncertainty. Peatlands are key landscape hotspots for MeHg production, however, the impact of climate warming on Hg cycling in boreal peatlands is not well studied. We use a multi-year field-based warming experiment (2 years passive, 1 year active ground warming) across two boreal peatland types (moss and sedge dominated) to explore the effects of ground warming on inorganic Hg (IHg) release, net MeHg production, and biogeochemical controls on both of these processes including the availability of sulfate and dissolved organic matter quality and concentration.